Collaborative learning tools (main module) / Chin Wan Sin - Chin , Wan Sin (2002)
With the rapid change of technological, it is not astonishing that the teaching and learning approach is also having its evolution era. In fact, traditional methods are not enough to support or fulfill nowadays-educational world anymore. Thus, through the studies and researches result show that collaborative learning is one of the suggested teaching and learning approach.